2000
DOI: 10.1093/wbro/15.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Institutions: A Review of the Evidence

Abstract: Africa's disappointing economic performance, the East Asian financial crisis, and the weak record of the former Soviet Union have focused attention on the role of institutions in determining a country's economic growth. This article critically reviews the literature that tries to link quantitative measures of institutions, such as civil liberties and property rights, with growth of gross domestic product across countries and over time. An important distinction is made between indicators that measure the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
276
0
23

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(305 citation statements)
references
References 61 publications
6
276
0
23
Order By: Relevance
“…For a recent survey and critique of such measures used in the growth literature, see Aron (2000). Related surveys include Alesina and Perotti (1994), Brunetti (1997), and Deaton and Miller (1996).…”
Section: Empirical Evidence Linking Institutions and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…For a recent survey and critique of such measures used in the growth literature, see Aron (2000). Related surveys include Alesina and Perotti (1994), Brunetti (1997), and Deaton and Miller (1996).…”
Section: Empirical Evidence Linking Institutions and Growthmentioning
confidence: 99%
“…Private sector investment or risk ratings have achieved prominence in influencing the net flows of international private capital to these countries. Ratings comprise weighted indexes reflecting both a country's macroeconomic and financial performance and prospects, and subjective assessments of institutional factors such as the degree of bureaucratic delays, corruption, respect of property and contract enforceability (see Aron 2000: Table 1). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding that some of the explanatory variables are not institutions and that institutional quality variables suffer for issues of aggregation, in his survey article, Aron (2000) pointed towards a number of studies that showed significant correlation between development measures and institutional quality variables (Shirley, 2008;p. 626).…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the last decade, dozens of empirical papers purporting to present evidence in support of the claim have been published (Aron, 2000 is an early overview on the connection between institutions and growth). A more precise version of the phrase might be that 'institutions matter crucially for economic development'.…”
Section: Introductionmentioning
confidence: 99%